In the Beginning was the Image The Omnipresence of Pictures : Time, Truth, Tradition - Benedek, András; Veszelszki, Ágnes (Peter Lang International Academic Publishing Group, 2016)
The authors outline the topic of visuality in the 21st century in a trans- and interdisciplinary theoretical frame from philosophy through communication theory, rhetoric and linguistics to pedagogy. As some scholars of visual communication state, there is a significant link between the downgrading of visual sense making and a dominantly linguistic view of cognition. According to the concept of linguistic turn, everything has its meaning because we attribute meaning to it through language. Our entire world is set in language, and language is the model of human activities. This volume questions the approach in the imagery debate.